Surgery of the aortic root: should we go for the valve-sparing root reconstruction or the composite graft-valve replacement is still the first choice of treatment for these patients? - Lamana,Fernando de Azevedo (2015)
AbstractObjective:To compare the results of the root reconstruction with the aortic valve-sparing operation versus composite graftvalve replacement.Methods:From January 2002 to October 2013, 324 patients underwent aortic root reconstruction. They were 263 composite graft-valve replacement and 61 aortic valve-sparing operation (43 reimplantation and 18 remodeling). Twenty-six percent of the patients were NYHA functional class III and IV; 9.6% had Marfan syndrome, and 12% had bicuspid aortic valve. There was a predominance of aneurysms over dissections (81% vs. 19%), with 7% being acute dissections. The complete follow-up of 100% of the patients was performed with median follow-up time of 902 days for patients undergoing composite graft-valve replacement and 1492 for those undergoing aortic valve-sparing operation.Results:In-hospital mortality was 6.7% and 4.9%, respectively for composite graft-valve replacement and aortic valve-sparing operation (ns). During the late follow-up period, there was 0% moderate and 15.4% severe aortic regurgitation, and NYHA functional class I and II were 89.4% and 94%, respectively for composite graft-valve replacement and aortic valve-sparing operation (ns). Root reconstruction with aortic valve-sparing operation showed lower late mortality (P=0.001) and lower bleeding complications (P=0.006). There was no difference for thromboembolism, endocarditis, and need of reoperation.Conclusion:The aortic root reconstruction with preservation of the valve should be the operation being performed for presenting lower late mortality and survival free of bleeding events.